Highly Durable Membrane Electrode Assembly with Multiwalled Carbon Nanotubes/CeO2‐Reinforced Nafion Composite Membrane by Spraying Method for Fuel Cell Applications. Issue 9 (19th March 2022) - Choi, Eunho; Kim, Sang Moon; Jang, Segeun
Abstract: For achieving economically viable polymer electrolyte membrane fuel cells (PEMFCs) in the commercial market, simplifying the fabrication process and manufacturing of robust membrane electrode assembly (MEA) are important. Herein, a single spray‐coating method for developing a robust and free‐standing reinforced Nafion composite membrane and electrodes is reported. By comparing the fabricated membrane's morphology under diverse process conditions including the nozzle‐to‐substrate distance and solution‐loading rates, the optimized spray‐coating for uniformly deposited spray‐based membrane without any defects has been determined. To explain this optimized condition, a simple theoretical model based on the concept of the surface coverage of sprayed droplets is proposed. The fabricated multiwalled carbon nanotubes/CeO2 ‐reinforced Nafion composite membrane shows excellent mechanical properties with minimal proton‐conducting loss despite using additional fillers of total 4 wt% in the Nafion matrix. By successively depositing the catalyst layer on that membrane using the same spray‐coating device, an MEA with the reinforced spray‐based membrane has been successfully fabricated; moreover, diverse electrochemical measurements and durability tests have been conducted. The MEA with the reinforced membrane shows comparable initial performance and considerably higher performance after the durability test compared to the MEA with commercial Nafion membrane. Abstract : The highly durable membrane‐electrode assembly (MEA) with multiwalled carbon nanotubes/CeO2 Nafion composite membrane is manufactured using a single spray‐coating method. The optimized spraying condition is experimentally and theoretically investigated, and the significantly improved durability of the MEA with the reinforced membrane is observed using diverse electrochemical measurements compared to the commercial Nafion membrane.